The Peristaltic Flow of Williamson Fluid through a Flexible Channel - Al-Khafajy , Dheia; Al-Delfi, Walaa N. (Iraqi Journal of Science, 2023)
The purpose of this study is to investigate the effect of an elastic wall on the peristaltic flow of Williamson fluid between two concentric cylinders, where the inner tube is cylindrical with an inelastic wall and the outer wall is a regular elastic sine wave.  For this problem, cylindrical coordinates are used with a short wavelength relative to channel width for its length, as well as the governing equations of Williamson fluid in the Navier-Stokes equations. The results evaluated using the Mathematica software program. The Mathematica program used by entering the various data for the parameters, where the program shows the graphs, then the effect of these parameters became clear and the results mentioned in the conclusion. Williamson fluid peristaltic flow through an elastic conduit is the subject of this investigation. For a number of significant elements, such as velocity distribution, stress and wave frame streamlines, graphic findings are supplied at the end of the article.